2020
DOI: 10.3892/etm.2020.9574
|View full text |Cite
|
Sign up to set email alerts
|

Identification of thrombomodulin as a dynamic monitoring biomarker for deep venous thrombosis evolution

Abstract: It has been demonstrated that thrombomodulin (TM) serves an important role in the formation of deep venous thrombosis (DVT) and is regarded to be a marker that can be used to measure vascular endothelial cell damage. However, how TM levels change during DVT evolution has not yet been well understood. The current study aimed to investigate the dynamic changes of TM during the evolution of DVT and explore the possible mechanisms behind these. A total of 48 patients newly diagnosed with DVT and 23 matched healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In this study, vascular tissues in contact with bone cement were selected to compare the influence of ES-PMMA and PMMA on the expression of thrombosis-related proteins in vascular endothelial cells and to illustrate the difference in the influence of these two types of bone cement on thrombosis by measuring the expression of these proteins. Among the many proteins expressed by endothelial cells, endothelin [ 15 ], vascular endothelial cell adhesion molecule [ 16 ], CD62p [ 17 , 18 ], CD31 [ 19 ], thermoregulatory protein [ 20 , 21 ], and CD40 [ 22 , 23 ] are closely related to thrombosis. We assessed the differential expression of thrombus-related proteins in endothelial cells by RT–qPCR and Western blotting and found that the expression of CD40 in the M group was significantly lower than that in the Con group.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, vascular tissues in contact with bone cement were selected to compare the influence of ES-PMMA and PMMA on the expression of thrombosis-related proteins in vascular endothelial cells and to illustrate the difference in the influence of these two types of bone cement on thrombosis by measuring the expression of these proteins. Among the many proteins expressed by endothelial cells, endothelin [ 15 ], vascular endothelial cell adhesion molecule [ 16 ], CD62p [ 17 , 18 ], CD31 [ 19 ], thermoregulatory protein [ 20 , 21 ], and CD40 [ 22 , 23 ] are closely related to thrombosis. We assessed the differential expression of thrombus-related proteins in endothelial cells by RT–qPCR and Western blotting and found that the expression of CD40 in the M group was significantly lower than that in the Con group.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of local thrombosis caused by high viscosity bone cement is that bone cement directly contacts with blood components or acts on vascular endothelial tissue. In this study, the vascular tissues in contact with bone cement were selected to compare the in uence of new high-viscosity bone cement and ordinary highviscosity bone cement on the expression of thrombosis related proteins in vascular endothelial cells, and to illustrate the difference of the in uence of these two high-viscosity bone cements on thrombosis by measuring the expression of these proteins.Among many proteins expressed by endothelial cells, endothelin [34,35], vascular endothelial cell adhesion molecule [36,37], CD62p [38,39], CD31 [40,41], thromboregulatory protein [42][43][44], and CD40 [45][46][47] are closely related to thrombosis. We detected the differential expression of endothelial cells and thrombus related proteins by RT-qPCR and WesternBlot, and found that the expression of CD40 in M group was signi cantly lower than that in Con group, which was statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TM can reflect the progression of DVT and has a good prognostic effect. 39 Studies have revealed that TM has good sensitivity and specificity in the diagnosis of DVT in Asian populations. 40 THBD c1418 C>T polymorphisms was not associated with the risk of PE, which may be due to the lack of included studies.…”
Section: Discussionmentioning
confidence: 99%